Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1063/1.4887058
|View full text |Cite
|
Sign up to set email alerts
|

Higher than 60% internal quantum efficiency of photoluminescence from amorphous silicon oxynitride thin films at wavelength of 470 nm

Abstract: Articles you may be interested inPhotoluminescence properties and crystallization of silicon quantum dots in hydrogenated amorphous Si-rich silicon carbide films Effect of thickness on the photoluminescence of silicon quantum dots embedded in silicon nitride films

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 29 publications
(14 reference statements)
0
27
0
Order By: Relevance
“…They believed that the PL arose either from radiative recombination between localized bandtail states associated with Si-N bonds similar to a-SiN x films or from both band-tail states and luminescent defect states, which consist of silicon sub-oxide bonding defects. However, in our previous works [44,46,49], the a-SiN x O y films were prepared by PECVD with NH 3 :SiH 4 :N 2 reaction gases, and then subsequently oxidized in situ by oxygen plasma [53]. As the O/(O+N) ratio is able to be controlled in the range of 0.05-0.15, and these a-SiN x O y films can be called as N-type a-SiN x O y films.…”
Section: Role Of Oxygen Bonding and N-si-o Bonding Defectsmentioning
confidence: 99%
“…They believed that the PL arose either from radiative recombination between localized bandtail states associated with Si-N bonds similar to a-SiN x films or from both band-tail states and luminescent defect states, which consist of silicon sub-oxide bonding defects. However, in our previous works [44,46,49], the a-SiN x O y films were prepared by PECVD with NH 3 :SiH 4 :N 2 reaction gases, and then subsequently oxidized in situ by oxygen plasma [53]. As the O/(O+N) ratio is able to be controlled in the range of 0.05-0.15, and these a-SiN x O y films can be called as N-type a-SiN x O y films.…”
Section: Role Of Oxygen Bonding and N-si-o Bonding Defectsmentioning
confidence: 99%
“…Silicon-based light-emitting materials have attracted attention over the past decade for their potential as next-generation Si photonics. Silicon-based materials, including silicon nitride (SiN x ) [1][2][3], silicon oxide (SiO x ) [4][5][6][7][8][9][10], silicon oxynitride (SiN x O y ) [11][12][13][14], and silicon oxycarbide (SiC x O y ) [15][16][17][18], show promise as CMOS-compatible integrated light sources. Thus, significant research efforts have been devoted to understand and optimize their structural and optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…13 Last year, the internal quantum efficiency of PL at the peak wavelength of about 470 nm has been achieved as high as 60%. 14 The present research is focused on the effect of oxygen incorporation into Si-N network and the role of N-Si-O bonding configuration in the tunable PL characteristics, thereby to identify the exact radiative recombination mechanism for the PL from our aSiN x :O samples. Through the x-ray photoelectron spectroscopy (XPS), electron paramagnetic resonance (EPR), and photoluminescence excited (PLE) measurements, it is found that the incorporation of oxygen atoms into Si-N network not only reduced the band tail structure disorder (Urbach tail energy, E U ) but also created N-Si-O (N x ) defect states in the band gap.…”
mentioning
confidence: 99%